ANALISIS PENGARUH PERSPEKTIF DAN MOTIVASI PEGAWAI NEGERI SIPIL TERHADAP KARIR DI LEMBAGA KESEHATAN PENERBANGAN DAN RUANG ANGKASA (LAKESPRA SARYANTO) JAKARTA - Bambang B Sulistiyono; Joko Supriyanto (JURNAL MITRA MANAJEMEN, 2017)
AbstractHealth Institute of Aeronautics and Space (LAKESPRA) Saryanto Jakarta is an institution that has a strategic role in the field of aerospace. which has primary responsibility for carrying out a medical examination of the crew military and civilian aircraft and became a scientific reference for the aviation community including health study in the field of space in Indonesia. Lakespra staffed by military personnel and civilian employees who both have the same roles and responsibilities since the complement policies implemented. However, in reality civil servants until now all excited to achieve high performance, it is characterized by low motivation and their perspective in viewing the future of his career. The results showed the group of women had a better motivation and perspective in view of his future, which reached 51% of the men. Similarly, a group of highly educated S2 has the highest motivation and perspective compared to the pass DIII and S1. From the results of the study provide a schematic and perspective and understanding that the factors motivating factors have a crucial role in supporting employee career at Lakespra. Keywords: Perspective, motivation, career.